KAJIAN POTENSI ASAP CAIR DALAM MENGENDALIKAN ULAT KROP KUBIS, Crocidolomia pavonana STUDY ON POTENCY OF LIQUID SMOKE AGAINST THE CABBAGE HEAD CATERPILLAR, Crocidolomia pavonana - , Wiyantono; Minarni, Endang Warih (Pembangunan Pedesaan, 2009)
The aim of this research was to seek raw materials for preparing liquid smoke, and then evaluated in laboratory for knowing its effects on feeding, development and mortality of the cabbage head caterpillar, Crocidolomia pavonana (F.) (Lepidoptera: Pyralidae) on cabbage. Antifeedant activity of the liquid was tested against third-instar of the caterpillar larvae with leaf residual method in leaf disc no-choice tests and contact method. Result of the research showed that the liquid at concentration from 3 - 22% reduced feeding by 22.94 - 51.52%, and prolonged period of the caterpillar development to pupation by 0.27 - 0.33 days compared to controls. The effects of test liquid smoke on mortality of Crocidolomia pavonana third-and fourth (final)-instar larvae were fed for 48 h broccoli leaves treated with a leaf residual and dipping method. The result show that the treatment 3 - 22% liquid smoke was not caused larvae death. The effects of liquid smoke from coconut shell (a raw material of the chosen few) was to take possession of antifeedant activity from weak to moderate against C. pavonana larvae.The effects of antifeedant from weak to moderate were the liquid at concentration from 3 - 22%. All the above effects could not give substantial suppression of C. pavonana population if the liquid was used in the field.